2022
DOI: 10.3389/fimmu.2021.787033
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Atlantic Salmon (Salmo salar) Skin in Response to Sea Lice and Infectious Salmon Anemia Virus Co-Infection Under Different Experimental Functional Diets

Abstract: Sea lice (Lepeophtheirus salmonis) are ectoparasitic copepods that cause significant economic loss in marine salmoniculture. In commercial salmon farms, infestation with sea lice can enhance susceptibility to other significant pathogens, such as the highly contagious infectious salmon anemia virus (ISAv). In this study, transcriptomic analysis was used to evaluate the impact of four experimental functional feeds (i.e. 0.3% EPA/DHA+high-ω6, 0.3% EPA/DHA+high-ω6+immunostimulant (IS), 1% EPA/DHA+high-ω6, and 1% E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…However, our results do not provide clear support for the importance of the complement immune response to sea lice resistance. This is consistent with previous observations of both the upregulation [139,147] and downregulation [104] of complement proteins in Atlantic salmon in response to sea lice. Our results therefore support earlier suggestions that activation of the complement pathway may not be sufficient to grant sea lice immunity in Atlantic salmon [139].…”
Section: Immune Responsesupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results do not provide clear support for the importance of the complement immune response to sea lice resistance. This is consistent with previous observations of both the upregulation [139,147] and downregulation [104] of complement proteins in Atlantic salmon in response to sea lice. Our results therefore support earlier suggestions that activation of the complement pathway may not be sufficient to grant sea lice immunity in Atlantic salmon [139].…”
Section: Immune Responsesupporting
confidence: 93%
“…Both species were reared in a Recirculating Aquaculture System at the Center for Aquaculture Technologies (PEI, Canada) in freshwater until post-smolt stage (approximately 15 g), after which fish were gradually transferred to saltwater and reared to a target weight of approximately 25 g. During the experiment, fish were kept in 135 L tanks at approximately 12 °C. Triplicate tanks of each species were treated with locally-sourced (n = 49 / fish, [147]) Lepeophtheirus salmonis Page: 24 copepodids and maintained for 60 hours and sampled every 12 hours. Untreated control fish were maintained in parallel tanks and sampled at 36 hours into the experiment.…”
Section: Experimental Designmentioning
confidence: 99%
“…conducted a transcriptomic analysis of sea lice ( Lepeophtheirus salmonis ) and infectious salmon anemia virus (ISAv) co-infection of the Atlantic salmon ( Salmo salar ) skin. The study found that the up-regulated genes were associated with glycolysis, the interferon pathway, complement cascade activity, and heat shock protein family, while the down-regulated genes were related to antigen presentation and processing, T-cell activation, collagen formation, and extracellular matrix ( 15 ). Co-infection of sea lice ( Lepeophtheirus salmonis ) with formalin-killed Aeromonas salmonicida activated the pathways involved in the innate (e.g., neutrophil degranulation) and adaptive immunity (e.g., antibody formation), and endothelial cell migration ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kim, Park, Kwon and Park [ 75 ] showed that the expression of chemokines and chemokine-related genes ( ccl19a.1 , cxl10 and ccl19 ) increased in the kidneys of flounder infected with VHSV. In addition, the expression levels of several pro-inflammatory chemokine genes ( ccl19 and ccl20 ) in Atlantic salmon were increased via immunostimulants (often pathogen-associated molecular patterns), and the chemokine genes ( ackr3 , ackr4 and ccr9 ) were upregulated after infectious salmon’s anaemia virus infection [ 78 ]. In the present study, the expression levels of ccl19a.1 , cxl10 , ccl19 , cxcl12a , ccl25b , ccl20a.3 , cxcl9 , ackr3b , ackr4b and ccr9 did not differ between the RTF1 and ASF groups.…”
Section: Discussionmentioning
confidence: 99%